Application of Sliding Mode Control Technique to Regulate DC/DC Boost Converters in Systems Exploiting Photovoltaic Power Generation - Le Tien Phong; Ngo Duc Minh (Institute of Advanced Engineering and Science, 2018)
This paper introduces a new method, called IB-SMC method, to control DC/DC boost converters in systems exploiting photovoltaic power generation. This method combines the sliding mode control technique and iterative-bisectional technique in the maximum power point tracker to change operations modes of photovoltaic power generation. The IB-SMC controller uses voltage sliding surface to evaluate the relation of instantaneous voltage at the input converter and instantaneous voltage at the maximum power point. Using information about the power of electromagnetic radiation from a pyranometer and temperature from a temperature sensor, the sliding surface and hyteresis band are changed by practically operational conditions that help improving energy efficiency of the process exploiting PVg. Simulations are carried out by Matlab/Simulink that show the ability to ensure dynamic stability by tracking instaneous maximum power point at any time whenever having any change of the operational condition, static stability by maintaining the operation point at maximum power point whenever not have any change of the operational condition and help to bring out approximately absolute energy efficiency.